Combined Scattering of Concurrent Unusual High‐Frequency EMIC Waves and MS Waves on Radiation Belt Electrons. Issue 13 (29th June 2022) - Zhou, Ruoxian; Fu, Song; Gu, Xudong; Ma, Xin; Ni, Binbin; Yi, Juan; Guo, Yingjie; Guo, Deyu; Jiao, Luhuai; Yun, Xiaotong; Wang, Xiaoyu
Abstract: We report a concurrent event of unusual high‐frequency Electromagnetic ion cyclotron (EMIC) and Magnetosonic (MS) waves in correspondence with butterfly distributions for sub‐MeV electrons and flux decay of MeV electrons, observed by Van Allen Probe A on 16 October 2017. The scattering effects are quantitatively investigated by test particle simulations. The results indicate that the unusual EMIC waves mainly scatter electrons from hundreds of keV to several MeV at pitch angles <60° while the MS waves mainly influence sub‐MeV and MeV electrons at pitch angles >60°. Their combined scattering effects are suitably analyzed to be justified as the linear superposition of the effect induced by each wave mode. The Fokker‐Planck simulations exhibit the formation of butterfly pitch angle distributions for sub‐MeV electrons and the obvious flux decay for electrons ∼1.8 MeV at all pitch angles, showing similar variation trends to the observations. Our study suggests that the occurrence of the two waves can significantly influence the electrons over the whole pitch angle range, which can help us better understand the radiation belt dynamics. Plain Language Summary: Electromagnetic ion cyclotron (EMIC) waves and Magnetosonic (MS) waves are commonly observed in the Earth's magnetosphere and play important roles in energetic electron dynamics. Usually, EMIC waves and MS waves scatter electrons at different energies and pitch angles. The peak frequency of the H + band EMIC wave is usually much lower than the equatorial proton gyrofrequency. Recently, a different type of H + band EMIC waves, named unusual high‐frequency EMIC waves since their peak frequency is close to the equatorial proton gyrofrequency, has been reported. Studies on the unusual high‐frequency EMIC waves found that these waves are capable of scattering sub‐MeV and MeV electrons that can also be influenced by MS waves. Moreover, observations confirm that unusual high‐frequency EMIC waves can be well connected with MS waves. In the present study, we quantitatively investigate the combined scattering effect of both wave modes on radiation belt electrons and simulate the evolution of the electron phase space densities under the impact of both waves. The simulation results show similar evolution trends as the observations, indicating the importance of incorporating these two waves and evaluating their combined effects on radiation belt particle dynamics. Key Points: Concurrent unusual high‐frequency Electromagnetic ion cyclotron (EMIC) and Magnetosonic (MS) waves are observed with butterfly pitch angle distributions (PADs) of sub‐MeV electrons and flux decay of MeV electrons The two wave modes can simultaneously affect sub‐MeV and MeV electrons, leading to significant pitch angle scattering The combined effect of both wave modes can form distinct butterfly PADs of sub‐MeV electrons and produce flux decay of MeV electrons